2008
DOI: 10.1542/peds.2007-3735
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A33 Is Associated With Susceptibility to Enterovirus 71 Infection

Abstract: The authors have indicated they have no financial relationships relevant to this article to disclose. What's Known on This SubjectEnterovirus 71 has caused large epidemics of disease, resulting in many fatalities and severe sequelae, in Taiwan and some other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…73,74,85 One genetic study in Taiwan reported that HLA-A33 is associated with increased susceptibility to EV71 infection, although the role of MHC remains unknown. 86 The researchers noted that HLA-A33 is more frequent in Asian populations than in white populations, which might explain the high number of EV71 epidemics in Asia. They suggested also that HLA-A2, in a mechanism yet to be defi ned, could be linked to the risk of cardiopulmonary failure in patients with EV71.…”
Section: Host Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…73,74,85 One genetic study in Taiwan reported that HLA-A33 is associated with increased susceptibility to EV71 infection, although the role of MHC remains unknown. 86 The researchers noted that HLA-A33 is more frequent in Asian populations than in white populations, which might explain the high number of EV71 epidemics in Asia. They suggested also that HLA-A2, in a mechanism yet to be defi ned, could be linked to the risk of cardiopulmonary failure in patients with EV71.…”
Section: Host Susceptibilitymentioning
confidence: 99%
“…They suggested also that HLA-A2, in a mechanism yet to be defi ned, could be linked to the risk of cardiopulmonary failure in patients with EV71. 86 The CTLA4 gene is an important regulator of T-cell cytotoxicity, and it has a role in the regulation of an immune response. In a study of 78 children with EV71 infection in Taiwan, those with meningoencephalitis had a higher frequency of G/G genotype at position 49 of exon 1 in this gene, than those without meningoencephalitis and controls.…”
Section: Host Susceptibilitymentioning
confidence: 99%
“…Severe and fatal EV71 infections are predominantly found in young children, with male patients outnumbering female patients (12,52). There has been a substantial increase in the frequency and severity of EV71 epidemics in recent years, particularly in the Asian Pacific region (5,13,58,65), prompting urgent, ongoing investigations of the virological and host factors contributing to the apparently increasing pathogenicity of the virus (5,11,58).…”
mentioning
confidence: 99%
“…However, 80% of EV71-infected patients become positive for EV71-specific neutralizing Abs 1 d after the onset of illness, and the magnitude of Ab responses are not correlated with disease severity and outcome (19). In contrast, documented clues imply that cellular but not humoral immune responses are correlated with disease progression and clinical outcome (20,21).…”
mentioning
confidence: 99%